Sosialisasi dan Pendampingan SK Nomor 0424/I/BS.00.01/2022 tentang Ejaan Bahasa Indonesia yang Disempurnakan untuk Perbaikan Tata Kelola Persuratan bagi Perangkat Desa di Kabupaten Magelang - Sri Hastuti; Kundharu Saddhono; Budhi Setiawan; Muhammad Rohmadi; Raheni Suhita; Ani Rakhmawati (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
The enactment of Law No. 24 of 2009 concerning Flags, Languages and State Symbols and the National Anthem which is confirmed by PP No. 57 of 2014, Minister of Education and Culture Regulation No. 42 of 2018, and SK No. 0424/I/BS.00.01/2022, of course, must be obeyed by all Indonesian citizens. Governance of correspondence in government agencies is one that is regulated in the law, in particular Article 33 paragraph 1 which reads